A first principle study of magnetic and opto-electronic properties of half metallic Heusler alloy, Co2TiSi. (2021) - Kumar, Arvind; Singh, Pawan K.; Sadiq, Mohd; Pal Singh, Rishi
Abstract: We have investigated the half metallic Heusler alloy, Co2 TiSi via first principle calculation using the Wien2K code and studied the electronic, magnetic and optical properties. Density of state (DOS) profile represents the half metallic character for Co2 TiSi i.e, 100% spin polarization at the Fermi level. Partial (p-) DOS show that major contribution is due to Co-3d and Ti-3d states across the Fermi level. Band structure also shows a band gap of ~ 1.0 eV for spin down states whereas metallic character for the spin up states. Calculated electronic and magnetic behavior along with estimated magnetic moment (1.98 μB ) found to be in good agreement with its experimental results.